ОЛИЙ ТИББИЙ ТАЪЛИМНИНГ УМУМИЙ ТЕНДЕЦИЯЛАРИ ВА ҚОНУНИЯТЛАРИНИ РИВОЖЛАНТИРИШДА ПЕДАГОГИКА ФАНИНИНГ ЎРНИ - Кадирова, М.Р. (SCIENCE and SOCIETY, 2021)
This article discusses the general trends in medical education for students, the development of pedagogy in medicine, the views of scientists on the differences between teachers and doctors, the organization of the educational process in medical education, the formation of ethical qualities in medical education, medical culture and professional culture. The peculiarities of professional culture are studied.